The Value of Leadership Rounding - M. Maureen Lal (JONA: The Journal of Nursing Administration, 2026)
Rounding is a foundational tool within the leadership toolbox. When executed effectively, it enhances nurse and patient engagement while improving patient safety outcomes. Rounding creates intentional opportunities for nurse leaders to connect with care team members. It also reinforces a culture of excellence through Magnet leader visibility, accessibility, and presence.